Avaliação da Experiência do Telespectador na Transição para a TV Orientada a Aplicativos - Shuen, Li-Chang; Soares Neto, Carlos de Salles; Moreno, Marcelo Ferreira; Bentivi, Zefinha; Gonçalves, João Victor Cruz; Costa, Iago Victor Silva (Anais Estendidos do Simpósio Brasileiro de Sistemas Multimídia e Web (WebMedia), 2024)
This position paper aims to evaluate the viewer experience during the transition to app-driven digital TV. Using focus groups and individual assessments, complemented by a quantitative survey, the research initially aimed to understand the average viewer’s assessment. However, important nuances were identified concerning populations experiencing digital exclusion, which were addressed with complementary qualitative investigation. The results highlight both the positive reception and specific difficulties faced by average viewers and viewers in situations of digital vulnerability.